Influence of atmospheric modes of variability on a deep lake south of the Alps - Salmaso, Nico (Climate Research, 2012)
Limnological measurements and winter air temperatures recorded in a deep lake south of the Alps (Lake Garda) have been analysed and related to temporal variations in five teleconnection patterns, i.e. the East Atlantic pattern (EA), the Eastern Mediterranean Pattern (EMP), the North Atlantic Oscillation (NAO), the Scandinavia pattern (SCAND) and the East Atlantic/West Russia Pattern (EA/WR). EA and EMP played a significant role in winter in the large-scale atmospheric circulation over the Mediterranean region. Positive and negative EA, and negative and positive EMP phases were closely connected with the development of mild and harsh winters, respectively. In turn, harsh winters had a strong and positive impact on the development of diatoms in spring and cyanobacteria in summer and autumn. These modifications were controlled through a linked chain of factors, which included lower winter lake water temperatures, deep lake circulation episodes, and higher replenishment of epilimnetic phosphorus at spring overturn. For the first time, this work demonstrates the existence of a strong connection between large-scale climatic fluctuations over the Mediterranean area and the temporal variations in the limnological characteristics of the large lakes located between the Alps and the northern border of the Mediterranean region. By converse, NAO, SCAND and EA/WR did not show any relationship with the winter climate and the limnological characteristics of Lake Garda.